2020
DOI: 10.1093/schizbullopen/sgaa045
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Suppression and Sensitivity for Motion in Schizophrenia

Abstract: Perceptual spatial suppression is a phenomenon in which the perceived strength of a stimulus in some region of the space is reduced when the stimulus is surrounded by other stimuli. For contrast perception, several studies suggest that spatial suppression is reduced in patients with schizophrenia. For motion perception, only one study has been conducted in a cohort of 16 patients, suggesting that spatial suppression is reduced. It is unknown, however, whether this reduction is related to the lower IQ that schi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Second, chin rests-which are often used when the experimental set-up consists of an external monitor connected to a desktop computer-could hardly be combined with mobile devices, hindering the maintenance of a constant viewing distance. To ameliorate this issue, in our previous studies (Linares et al, 2018(Linares et al, , 2020 the experimenter monitored the participants to ensure that they held the same approximate position during the test. A future solution to this issue could be the use of a facial recognition system like Face ID to measure the viewing distance and alert the participant if it changes during the test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, chin rests-which are often used when the experimental set-up consists of an external monitor connected to a desktop computer-could hardly be combined with mobile devices, hindering the maintenance of a constant viewing distance. To ameliorate this issue, in our previous studies (Linares et al, 2018(Linares et al, , 2020 the experimenter monitored the participants to ensure that they held the same approximate position during the test. A future solution to this issue could be the use of a facial recognition system like Face ID to measure the viewing distance and alert the participant if it changes during the test.…”
Section: Discussionmentioning
confidence: 99%
“…They are commonly carried out using software applications running on desktop or laptop computers, but running the software on mobile handheld devices such as smartphones or tablets could be advantageous in some situations. First, their small size and weight could facilitate their use outside the laboratory in places such as clinical environments (Kalia et al, 2014;Bastawrous et al, 2015;McKendrick, Chan, Vingrys, Turpin, & Badcock, 2018;Linares et al, 2020). Second, their touchscreen interface could facilitate their use by people with little experience with more traditional computers.…”
Section: Introductionmentioning
confidence: 99%
“…Although this notion has been supported by two subsequent studies [ 8 , 9 ], it was at variance with two other ones. The study by Linares et al [ 28 ] investigated the relationship between spatial suppression and intelligence using a between-group design that included a group of schizophrenia patients (N = 33) and a healthy control group (N = 31). The results revealed a link between spatial suppression and a measure of intelligence only in patients with schizophrenia, with no indication for such a relationship for the healthy control group.…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies exploring the physiological basis of these behavioral effects will be necessary to tease apart the separate contributions of acuity, attention, and orientation tuning in early cortical visual networks. 1), and because earlier studies have reported an association between IQ and perceptual surround suppression 32,[71][72][73][74] , we also investigated the association between IQ and task performance. While, across all groups, IQ did show a relationship with M (left panel: higher IQ predicts less dependence of suppression on orientation, after regressing out potential effects of acuity), IQ did not significantly moderate the relationship between group and M (F(4,119)=0.24, p=0.91, η²=.008).…”
Section: Discussionmentioning
confidence: 99%
“…In earlier work, PSZ have been measured to have a ∼50% reduction in perceptual suppression relative to controls for a task in which a low-contrast drifting center grating was embedded in a high-contrast surround grating drifting in the same direction with no explicit boundaries between center and surround 7,32 . The introduction of additional, explicit boundaries (a gap, a direction difference, or an orientation change) reduced surround suppression for all groups by comparable amounts 7 .…”
Section: Introductionmentioning
confidence: 99%